Efektivitas Intervensi Pendidikan untuk Meningkatkan Literasi Keuangan Islam pada Mahasiswa: Studi Kasus di Universitas PTIQ Jakarta - Andi Iswandi (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research aims to investigate the effectiveness of educational interventions in enhancing Islamic financial literacy among students at PTIQ Jakarta University. A qualitative approach was employed through a case study within the university environment. Data was gathered through in-depth interviews and observations of students participating in the educational intervention program. The research findings indicate that educational interventions play a crucial role in improving students' understanding of Islamic financial principles, such as the prohibition of riba (interest), zakat (obligatory charity), and sharia-compliant investments. Students who participated in the educational intervention program showed improvements in their financial attitudes and behaviors aligned with Sharia principles. They were more inclined to utilize Sharia-based financial products and services in their daily lives. Additionally, the students' educational background, religious understanding, and social environment also influenced the effectiveness of the educational interventions. This study offers recommendations for educational institutions and policymakers to develop more creative and innovative educational intervention programs to enhance Islamic financial literacy among students. Furthermore, the research highlights the significant role of universities in equipping students with knowledge and understanding of Sharia finance to become agents of change, contributing to sustainable economic development in line with Islamic values.